Perubahan Dividen dan Catering Incentives - Setiawan, Rahmat; Yanuaristya, Nina; Andaran, Vanya Jossi (STIE AMKOP, 2024)
This research tests the extend of catering theory of dividend by using dividend changes including dividend increase and decrease. The purposes of this research are to determining the effect of catering incentives on the decision to increase and decrease dividends and the magnitude of the dividend increase and decrease. Based on the studies that have been conducted, there is still little research on testing the theory of dividend catering in companies in Indonesia. Previous research also used models that only included companies classified as dividend payers and non-payers, while companies are more often faced with decisions related to changes in the level of dividends paid than decisions to pay or not to pay dividends. On the basis of this phenomenon, this study further examines catering incentives and their effect on dividend changes. This research uses 106 non-financial companies listed on the Indonesian Stock Exchange during 2006–2013, with a sample size of 343 observations. The analysis techniques used in this study are logistic regression analysis and multiple linear regression using panel data. The results of the research showed that catering incentives measured by dividend premiums have a significant positive impact on decisions to increase dividends and a significant negative impact on decisions to decrease dividends. Furthermore, catering incentives have a significant positive impact on the magnitude of dividend increases and a significant negative impact on the magnitude of dividend decreases. Company management needs to consider dividend premiums to determine the demand of capital market investors on dividends with the aim of maximizing the market price of the company. Keywords: Catering, dividend policy, dividend changes